Conjecturing with some Conjectures (Global Journal of Science Frontier Research, 2020)
This world has been seeing so many conjectures from the formation of this world. Particularly, mathematics world has been seeing so many conjectures from the civilization of this world, also venturing through on it. So many Indians, Chinese and Arabian scholars provided their participation in mathematics world. Since before Euclid so many mathematicians ventured on numbers, geometry, astronomy, etc... in number theory, there are so many conjectures like applications of GCD, Fermat Last theorem, Euler's totient function, Gold Bach conjecture, ABC conjecture, etc... some of this has been proved but so many of that still has not been proved. In this paper, I try to prove Gold Bach conjecture, stating abc conjecture for composite numbers, and try to deliver some conjectures.
Keywords: GCD; euler2019; s totient function; gold bach conjecture; abc conjecture